Enhancing Students' Learning Motivation through the Integration of the TPACK Framework in Aqidah Akhlak Education - Inayati, Mahfida; Maimun, Maimun; Sa'diyah, Halimatus; Listiana, Heni (Maharot : Journal of Islamic Education, 2024)
Students' motivation to learn is very important in education. In the current digital era, teachers are able to keep up with the ability to integrate technology, pedagogy and moral beliefs through learning models. To answer this problem, research is carried out with a qualitative approach, a type of case study research. The research location was chosen by MAN 1 Pamekasan class X. Data collection is carried out by interviews, observations and documentation. Data analysis was carried out by analyzing sites to check the validity of data through credibility, transferability, dependability and objectivity tests. Research results The implementation of the TPACK framework-based model of a teacher is able to integrate technology, pedagogy and moral faith subjects. The implementation is found in learning resources, teaching materials, learning media and infrastructure. Students' motivation to learn with this has increased so that they can divide problems easily and help students in working on all problems. So that the average student score increases with an average of 90 as evidenced by achievements both academic, national and international.